Białoruskie środki masowej informacji – kryzys permanentny? - Musiał, Miron (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2005)
The paper describes the Belarussian legal system with reference to the mass media. The author attempts to track the evolution of the fundamental law as well as that of acts, decrees and ordinances that led to an authoritarian press system (according to the theory of Siebert, Schramm and Peterson) to emerge in Belarus. Legal acts were treated in anincreasingly instrumental way that became particu larly obvious in the above-mentioned realm of the media. This applied both to the stage of their emergence and management. The main principle of this tendency was the profound influence the media exert on peoples’ attitudes. The moment Alexander Lukashenka assumed the position of President of the Republic, he has started to impose the state control over the whole spectrum of relations within the society. The mass media have been among the first victims as their impact on the society was well evidenced. The authorities have not yet completely succeeded in subordinating the mass media to the state propaganda mechanisms; however there are unequivocal indications what the ultimate results the policy that has been consistently implemented since 1995 will bring. There are fewer than ten independent editorial offices in Belarus at present...
The Mass Media in Belarus - a Permanent Crisis?